The Performance of Sustainable Exchange-Traded Funds - Suvanto, Stella (My University, 2019)
Socially responsible investing (SRI) as well as passive asset management through exchange-traded funds (ETF) have increased their market size exponentially in recent years and affected significantly in many investors investing styles. SRI incorporates social, environmental and governance criteria to the investment decisions, while exchange-traded fund is a marketable financial security that typically track indexes, bonds, commodities or pool of assets like an index fund. This study investigates the combination of these two prevalent trends in financial markets and examines how sustainability affects the returns of ETF’s investments. This research investigates how sustainability level affects the performance of Exchange-traded funds in the U.S equity market. In this research ETF’s are classifieds into different portfolios based on Morningstar’s sustainability ratings. The empirical research is implemented by investigating how ETFs with different sustainability levels yield abnormal returns and how they perform compared to other sustainability classes. The methodology of this thesis consists of the CAP-model Fama-French three-factor and five-factor models, Carhart four-factor model and risk-adjusted performance measures Sharpe ration and Traynor ration. The empirical results suggest that the level of sustainability affects the performance of ETF investment. During the research periods 31.12.2013-31.10.2018 the most unsustainable portfolio and the most sustainable portfolio underperformed more conventional portfolios i.e. portfolios which perform averagely in sustainability. This suggest that when investing in highly sustainable ETFs or highly unsustainable ETFs in the U.S market, there is a greater risk of loss. However, if these extreme ETFs are rejected from the sample, the ETF’s abnormal return and the level of sustainability have a negative relationship.
Keywords: Socially Responsible Investing; Exchange-Traded Fund; Investment performance; Factor models; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|